Characterization of the novel HLA‐A*03:350 allele by sequencing‐based typing. (3rd June 2019) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Guidicelli, Gwendaline; Visentin, Jonathan
Abstract : HLA‐A*03:350 differs from HLA‐A*03:01:01:01 by one nucleotide substitution in codon 1 in exon 1.